CIRC ( Cooperative Integrated Reading and Composition) as Strategy of Teaching Reading Comprehension - Imam nur Aziz; Ninda Putri Cahyani (JEET, Journal of English Education and Technology, 2022)
The Cooperative Integrated Reading and Composition (CIRC) technique for teaching reading comprehension in a recount text environment is the subject of this study. Cooperative learning necessitates that students collaborate on a shared goal and coordinate their efforts. The study used a pre-experimental pretest-posttest design. Surabaya junior high students provided the samples. The result reveals that the value (2-tailed) is 0,000, indicating that the CIRC approach has a positive impact on pupils' reading comprehension. The mean of the pre-test experiment group was 50.00, while the standard of the post-test experiment group was 80'00. Students who were taught the Cooperative Integrated Reading and Composition (CIRC) technique outperformed those who were taught alternative strategies.